Solution route synthesis of dendrite Cu6Sn5powders, anode material for lithium-ion batteries - T. Sarakonsri (2018)
Intermetallic dendrite particles, such as Cu6Sn5compound, possible anode materials for high power lithium-ion batteries, can be synthesized by using solution technique. Solution route method can induce the formation of the compound by performing a redox reaction between metal chloride salts and metallic reducing powder in a suitable solvent. The morphological features and single-phase formation corresponding to different processing conditions including solvent type, reducing agent particle size, and reaction temperature, were determined. The X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) results illustrate the dendritic morphology of Cu6Sn5particles with small amount of impurities, which can be synthesized by using ethylene glycol as solvent and zinc powder as reducing agent. Reducing agent particle size and reaction temperature have a very small effect on the formation of the Cu6Sn5dendrite powder. © Springer Science+Business Media, Inc. 2006.